DETERMINATION OF SERUM GONADOTROPIN AND TESTOSTERONE LEVELS IN MALE INFERTILITY - Khan, Muhammad Shoaib; Ali, Irshad; Hussain, Mukhtiar; Nawaz, Khan; Zeb, Malik; Anwar, Wasim; Ullah, Azmat; Zada, Laiq; Javaid, Arshad (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the levels and ratios of serum LH, FSH and Testosterone, among men having history of infertility. Material and Methods: A non-interventional descriptive study was carried out in the Department of Public Health Laboratories Division, NIH, Islamabad from January 2004 to December 2005. Two hundred fifty infertile men, classified as azoospermic (50), oligozoospermic (75), asthenozoospermic (50) and normozoospermic (75) were studied for serum LH, FSH and Testosterone, in addition to 50 proven fathers. Results: The respective FSH (mIU/ml), LH (mIU/ml) and Testosterone (nmol/L) levels for the groups were 22.924.15, 13.852.33 and 11.860.70 (Azoospermia), 16.823.79, 10.921.22 and 11.88+1.06 (Oligozoospermia), 3.220.61, 3.921.17 and 16.24+2.05 (Asthenozoospermia) while in normozoospermic men were 5.530.52, 7.400.60 and 17.29+1.02, The proven fathers group had 7.74+0.71 mIU/ml LH, 6.75+1.06 mIU/ml FSH and 15.88+1.15 nmol/ml testosterone, respectively. The LH/FSH and FSH/LH ratios were 0.77+0.08 and 1.84+0.22 (Azoospermia), 1.78+0.41 and 1.47+0.18 (Oligozoospermia), 1.51+0.46 and 1.28+0.28 (Asthenozoospermia) while in normozoospermic and proven fathers were 1.55+0.16 and 0.85+0.10,1.67+0.22 and0.94+0.12. Similarly, the LH/T and T/LH ratios were 1.17+0.28 and 0.86+2.70 (Azoospermia), 0.92+0.28 and 1.08+0.17 (Oligozoospermia), 0.30+0.10 and 4.14+10.4 (Asthenozoospermia) and in normozoospermic were 0.42+0.08 and 2.34+0.48.The ratios observed for T/FSH and FSH/T were 0.52+0.17 and 1.93+5.95 (Azoospermia), 0.71+0.28 and 1.42+3.57 (Oligozoospermia), 5.04+3.38 and 0.20+0.30 (Asthenozoospermia) and in normozoospermic men were 2.82+0.90 and 0.35+1.12, while in proven fathers were 4.09+0.57and 1.04+0.53 respectively. Conclusion: Altered/disturbed concentrations of gonadotropins and androgenic hormones and their ratios cause infertility, since all these hormones act synergistically.